Legal safeguards for freedom of expression and the admissibility of information on the consequences of abortion – a comparative legal perspective - Pietrzak, Przemysław; Smulski, Kamil (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
This chapter addresses the issues related to the propagation of anti-abor tion views in selected countries around the world. Legal solutions and court decisions are discussed. Regulations and judgments guaranteeing freedom of speech, stating that various ways of presenting anti-abortion content are legal, are presented and contrasted with provisions and juris prudence limiting or even penalizing the dissemination of anti-abortion views due to the drastic form of the message or the place of their dissem ination (e.g., restrictions related to access zones). The study covers the legal systems of such countries as the United States of America, Canada, Australia, France and Poland.